Technical Guidance For The Preparation Of AKM-Based National Assessment Of English Learning for State Senior High School Teachers In Surabaya - Nunung Nurjati; Endah Yulia Rahayu; Samsul Khabib (Kanigara, 2022)
As a substitute for the National Examination (UN), the Ministry of Education and Culture (Kemendikbud) has prepared a National Assessment program. The National Assessment is a program to assess the quality of each school, madrasah, and equality program at the primary and secondary levels. The quality of the education unit is assessed based on the primary student learning outcomes (literacy, numeracy, and character), the quality of the teaching and learning process, and the climate of the academic unit that supports learning. The information was obtained from three main instruments: Minimum Competency Assessment (AKM), the Character Survey, and the Learning Environment Survey. Because this program is still limited to being introduced in the world of education as a substitute for the National Examination, there are still many things that the assessment implementer asks. Therefore, for the assessment of student learning outcomes, technical guidance for the teacher of SMA Negeri in Surabaya is arranged, which is expected to provide insight in the preparation of assessments that impact increasing students' critical thinking skills. This technical guidance is under community service activity from the faculty member of English Education Study Program.